Secreted Frizzled-Related Protein 2 and Extracellular Volume Fraction in Patients with Heart Failure. (7th May 2020) - Yang, Shaomin; Chen, Haixiong; Tan, Kuan; Cai, Fusheng; Du, Yongxing; Lv, Weibiao; Hu, Qiugen; Hu, Yunzhao; Huang, Yuli
Abstract : Background . Quantification of extracellular volume (ECV) fraction by cardiovascular magnetic resonance (CMR) has emerged as a noninvasive diagnostic tool to assess myocardial fibrosis. Secreted frizzled-related protein 2 (SFRP2) appears to play an important role in cardiac fibrosis. We aimed to evaluate the association between SFRP2 and myocardial fibrosis and the prognostic value of ECV fraction in patients with heart failure (HF). Methods . In this prospective cohort study, 72 hospitalized adult patients (age ≥ 18 years) with severe decompensated HF were included. CMR measurements and T1 mapping were performed to calculate ECV fraction. Serum SFRP2 level was detected by an enzyme-linked immunosorbent assay kit. All patients were followed up, and the primary outcomes were composite events including all-cause mortality and HF hospitalization. Results . During the median follow-up of 12 months, 27 (37.5%) patients experienced primary outcome events and had higher levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP), SFRP2, and ECV fraction compared with those without events. In Pearson correlation analysis, levels of SFRP2 (r = 0.33 ), high-sensitivity C-reactive protein (r = 0.31 ), and hemoglobin A1c (r = 0.29 ) were associated with ECV fraction (all P < 0.05 ); however, in multivariate linear regression analysis, SFRP2 was the only significant factor determined for ECV fraction (r partial = 0.33, P = 0.02 ). In multivariate Cox regression analysis, age (each 10 years, hazard ratio (HR) 1.13, 95% confidence interval (CI) 1.04–1.22), ECV fraction (per doubling, HR 1.68, 95% CI 1.03–2.74), and NT-proBNP (per doubling, HR 2.46, 95% CI 1.05–5.76) were independent risk factors for primary outcomes. Conclusions . Higher ECV fraction is associated with worsened prognosis in HF. SFRP2 is an independent biomarker for myocardial fibrosis. Further studies are needed to explore the potential therapeutic value of SFRP2 in myocardial fibrosis.